Comparative Analysis of VO₂ Max between Smokers and Non-Smokers in Football Players: A Study in an Amateur Club - Runesi, Salmon; Louk, Michael Johanes Hadiwijaya; Fufu, Ronald Dwi Arfian; Tajuddin, Al Ihzan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2025)
Smoking is a behavioral factor that can reduce athletic fitness, but the comparison of VO₂ max capacity between smokers and non-smokers in soccer players is still rarely studied. This study aims to analyze the differences in VO₂ max between two groups of players at Fortuna FC, Kupang. The study employed a quantitative comparative design involving 20 participants (10 smokers and 10 non-smokers). VO₂ max was measured using the Multistage Fitness Test (Beep Test) and analyzed using an independent sample t-test. The results showed a significant difference between the groups (t(18) = 8.639; p < 0.001), with a higher average VO₂ max in non-smokers (54.7 mL·kg⁻¹·min⁻¹) compared to smokers (48.9 mL·kg⁻¹·min⁻¹). This difference of 5.8 mL·kg⁻¹·min⁻¹ indicates a decrease in aerobic capacity of approximately 10–12% in smokers. These findings confirm that smoking negatively impacts the cardiorespiratory fitness of amateur soccer players. This study provides relevant empirical evidence for coaches and sports health professionals to promote smoking prevention programs in the development of athletes.